2005
DOI: 10.1080/15287390590921748
|View full text |Cite
|
Sign up to set email alerts
|

Contaminant Loads And Hematological Correlates In The Harbor Seal (Phoca vitulina) Of San Francisco Bay, California

Abstract: An expanding body of research indicates that exposure to contaminants may impact marine mammal health, thus possibly contributing to population declines. The harbor seal population of the San Francisco Bay (SFB), California, has suffered habitat loss and degradation, including decades of environmental contamination. To explore the possibility of contaminant-induced health alterations in this population, blood levels of polychlorinated biphenyls (PCBs), dichlorodiphenyldichloroethylene (DDE), and polybrominated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 49 publications
1
33
1
Order By: Relevance
“…Hematocrit in ranch mink (Mustela vison) exposed to a PBDE mixture was reported to be significantly lower compared with control mink [36]. Neale et al [37] found erythrocyte level to be inversely correlated to PBDE concentrations in harbor seal (Phoca vitulina). Based on those contradictory results for birds and mammals, we suggest that the blood system of a bird may be less sensitive to the effects of PBDE exposure, possibly because of hematological differences between those taxa [29].…”
Section: Discussionmentioning
confidence: 99%
“…Hematocrit in ranch mink (Mustela vison) exposed to a PBDE mixture was reported to be significantly lower compared with control mink [36]. Neale et al [37] found erythrocyte level to be inversely correlated to PBDE concentrations in harbor seal (Phoca vitulina). Based on those contradictory results for birds and mammals, we suggest that the blood system of a bird may be less sensitive to the effects of PBDE exposure, possibly because of hematological differences between those taxa [29].…”
Section: Discussionmentioning
confidence: 99%
“…Altered immune parameters associated with environmental exposure to PAHs and PCBs have been reported for several species of pinnipeds and cetaceans and include reduced antigen-specific antibody responses, depressed T-lymphocyte proliferative responses to mitogen, depressed plasma retinol, increased white blood cell count and depressed red cell parameters, and frequent infections with mildly pathogenic bacteria and high rates of cancer (Martineau et al 1994, Lahvis et al 1995, Beckmen et al 2003, Jenssen et al 2003, Neale et al 2005. Experiments in which captive harbor seals were fed heavily-contaminated (especially with PCBs) fish also supported a hypothesis of contaminant-induced immunological impairment.…”
Section: Introductionmentioning
confidence: 98%
“…Since marine mammals such as seals are positioned at the top of the marine food web and have a relatively long life span (25-30 years), they are exposed to organochlorines (Neale et al, 2005a;Shaw et al, 2005) and are consequently vulnerable to endocrine disruptive effects such as reproductive impairment (Reijnders, 1986;Reddy et al, 2001), cancer (Martineau et al, 2002;Ylitalo, 2005), thyroid alteration (Sormo et al, 2005;Tabuchi et al, 2006), and immune suppression/infectious diseases (Ross, 2002;Beckmen et al, 2003;Hall et al, 2006;Hammond et al, 2005). PCBs are stored in the insulating blubber (lipid) and can be subsequently remobilized to the blood through lipid metabolism during the seasonal fasting (Debier et al, 2006), posing a health risk.…”
Section: Introductionmentioning
confidence: 99%